Development of occupational safety and health (OSH) performance management framework for industries in Malaysia - Abdul Hamid, Suhaila (2022)
Each organisation should track occupational safety and health (OSH) performance to ensure that safety and health regulations are being followed and employers can address OSH concerns before they become a serious issue that affects everyone in the organisation. The purpose of this research is to build a framework for managing occupational safety and health performance based on Edgar Schein's organisational culture model and system theory of accident causation. This is a quantitative research study that utilises a questionnaire and is built based on the Occupational Safety and Health Act (OSHA) of 1994, ISO 45001:2018, and pertinent literature reviews. Eight industrial and academic specialists evaluated the questionnaire. The study employs purposive sampling of OSH competent individuals and OSH practitioners from companies covered by Schedule 1 OSHA 1994. The analysis included a total of 300 respondents. The Structural Equation Modelling (SEM) version 23 and the Statistical Package for the Social Sciences (SPSS) version 17 were used for data analysis, which included correlation, regression, and goodness of fit tests. The findings indicated that OSH leadership, support for OSH management, a risk reduction programme, and employees' OSH values all had a positive correlation with OSH performance. Additionally, mediators in the OSH performance management framework included OSH management support and risk reduction programmes, while the availability of OSH management systems acted as a moderator. Thus, the research successfully developed an OSH performance management framework that included seven OSH values and was transformed into an OSH balanced scorecard to enable employers to self-regulate OSH practises; achieve the preventive culture envisioned in the OSH Master Plan 2020; and embrace business sustainability.